A comparative study of endotracheal intubation as per intubation difficulty score, using Airtraq and McCoy laryngoscopes with manual-in-line axial stabilization of cervical spine in adult patients - Sarvaiya, Nilesh; Thakur, Deepali Pankaj; Tendolkar, Bharati Anil (International Journal of Research in Medical Sciences, 2017)
Background: The different types of laryngoscopes have been invented to improve the laryngoscopic view of the glottis in normal and difficult airway which helps anaesthesiologists to safeguard the airway during anaesthesia. Patients with cervical spine injury have deleterious compression forces on the spinal cord and that should be avoided by taking protective measures which include application of rigid collar, a forehead tape and manual-in-line axial stabilisation (MILAS). The objective of the study was to evaluate the ease of intubation with Airtraq and McCoy laryngoscope as per intubation difficulty score (IDS) with manual-in-line axial stabilization of cervical spine. Methods: In this prospective observational study, 100 adults of ASA I-II, aged 18 to 60 years, with Mallampati classification I and II, undergoing elective surgery under general anaesthesia with oral endotracheal intubation were included. Fifty patients were intubated using Airtraq (Group A). Another fifty patients were intubated using McCoy laryngoscope (Group B). During intubation with both devices, neck was immobilized using MILAS. Ease of intubation as per IDS, insertion of device as per Likert scale, duration of laryngoscopy and intubation, number of attempts, haemodynamic changes and complications were compared for both devices. Results: Demographic characteristics were comparable in both groups. There is no significant difference observed in the heart rate, systolic and diastolic blood pressure during device insertion, intubation and up to 10 minutes after intubation in Airtraq and McCoy group. There is statistically significant difference in number of intubation attempts, duration of laryngoscopy and intubation in both groups. As per Likert scale, ease of insertion of device was statistically insignificant between two groups. McCoy group had statistically significant higher intubation difficulty scores (2.9±0.68) compared to Airtraq group (0.56±0.54) (p=0.000). All patients in Airtraq group showed Cormack and Lehane grade 1, while 30% patients in McCoy group had Cormack and Lehane grade more than 1. Conclusions: The Airtraq facilitates the ease of intubation by providing a better view of the larynx as compared to McCoy laryngoscope in patients with manual-in-line axial stabilization of cervical spine.